New Zealand : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that the economic expansion in New Zealand is becoming increasingly embedded and broad based, with growth exceeding 3 percent in the second half of 2013. The drivers include supportive financial conditions, record high export commodity prices, resurgent construction activity related to the Canterbury post-earthquake rebuild and general housing shortages, and a substantial increase in net immigration. Growth is expected to increase to about 3 1\2 percent in 2014 and moderate to a trend rate of 2 1\2 percent over the medium term. Strong construction activity is expected to remain an important driver for near-term growth.